Model Pengujian Celah Keamanan Bug Host Pada Layanan Promosi Operator SelulerModel Pengujian Celah Keamanan Bug Host Pada Layanan Promosi Operator Seluler - Dedy Hariyadi; Imam Ahmad Subhan; Alfirst Radena Julio Vanca (INTEK : Jurnal Informatika dan Teknologi Informasi, 2018)
The growth of internet usage in Indonesia can not be separated from market penetration role by Cellular Operator. In this case Celullar Operators often provide promotional services to customers. Behind the promotional services there are several security holes that are utilized by customers. Usually the security hole is called a bug host. This research proposes a model of security testing of the promotional services.